Impact of Sentencing Reforms and Speedy Trial Laws in the United States, 1969-1989 - Marvell, Thomas B. ([Verlag nicht ermittelbar], 1992)
The certainty and promptness of punishment have long been hypothesized to be important variables in deterring crime. This data collection evaluates whether sentencing reforms to enhance certainty of punishment and speedy trial laws to enhance promptness of punishment affected crime rates, prison admissions, and prison populations. Variables include state, year, crime reports, economic conditions, population (including age structure), prison population, prison releases, and prison admissions. The unit of observation is the state by the year.